Children and Youth in Crisis : Protecting and Promoting Human Development in Times of Economic Shocks - Lundberg, Mattias; Wuermli, Alice (Washington, DC: World Bank, 2012)
Motivated by the need to understand how crises affect human development in diverse segments of the population, this book explores how individuals and households cope with the changes and stresses induced by economic crises. It examines how these impacts and coping mechanisms differ across cultural and institutional contexts and looks at how best to protect the most vulnerable from lasting harm and the degradation of human capital. Financial crises, at both the global and the national level, are ubiquitous. Reinhart and Rogoff (2009) provide the invaluable lesson that over the past 800 years a major crisis has happened roughly once every 20 years. This pattern raises concern about the human impacts of crises, especially among more vulnerable people in developing countries. During the most recent global financial crisis, international organizations, bilateral development agencies, and civil society organizations all expressed concern about the ongoing 'human crisis.' The global community has become alarmed that the crisis could reverse recent progress in poverty reduction and the achievement of the Millennium Development Goals. Human development is at the core of economic development. Human capital accumulation at all stages from the antenatal environment through early childhood and adolescence helps facilitate the transition to a healthy and productive adulthood and break the intergenerational transmission of poverty. Shortfalls or setbacks at any stage of the life course may have severe consequences for individual development as well as for the growth and development of successful communities. The work presented in this volume deepens our understanding of how shocks affect children and youth in two ways. First, the authors aggregate the evidence on various developmental outcomes across developmental stages from conception to adulthood. Second, the authors show that the impact of crises will differ according to the social and environmental contexts in which the child or young person grows and that shocks can in turn affect those contexts. The authors hope to understand the short- and long-term impacts of crises, and whether we can identify particular protective factors that support children's recovery from the worst ravages of the crisis. The focus on transmission mechanisms, the pathways of influence, leads to a set of broad policy recommendations for enhancing both protection and recovery.